Isolation and characterization of a dideoxyguanosine triphosphate-resistant mutant of human immunodeficiency virus reverse transcriptase. - Prasad, V R (1991)
The appearance of drug-resistant strains of viral pathogens is a major difficulty confounding current efforts to block viral infections. The identification and analysis of mutations responsible for drug resistance can provide important clues helpful in understanding the mechanisms of resistance and in the eventual development of better therapies. We have used a direct screening method to scan libraries of mutagenized genes encoding the reverse transcriptase of human immunodeficiency virus type 1, and have recovered a variant enzyme that is resistant to the chain-terminator inhibitor 2',3'-dideoxyguanosine triphosphate. The single substitution mutation in this variant conferred broad crossresistance to a variety of other antiviral compounds currently in clinical trials. Virus carrying the mutation was fully infectious in cultured human lymphocytes. The replication of the mutant virus was highly resistant to phosphonoformic acid but did not show increased resistance to the prodrug dideoxyguanosine.